Assessment of potential health impacts on surface water sources in Northern Nigeria - Umar, ZD; Bashir, A (International Journal of Environment, 2014)
Northern Nigeria represents the most populous region in Nigeria and adequate water supply and sanitation typically leaves a lot to be desired in the region in order to prevent water related diseases to the vulnerable communities of the region. This research work was carried out in Kano state with specific emphasis on Tomas dam which is one of the largest dams established for multipurpose use in Nigeria. The research was aimed at evaluating Physico-chemical and Bacteriological quality of Tomas Dam in Kano State. 240 water samples from 5 sampling stations within eight months were analyzed for bacteriological and physico-chemical quality. The physico-chemical parameters indicated Biochemical Oxygen Demand (BOD) and Water Current Speed results were not significantly different (P>0.05), while other physico-chemical parameters analyzed varied significantly (P<0.05). The study also revealed that Dissolved Oxygen (DO), BOD, Turbidity, and Nitrates recorded higher values than WHO and Federal Environmental Protection Agency, Nigeria (FEPA) limits. Total aerobic bacterial counts (TBC) and total coliform counts (TCC) were determined using pour plate and Most Probable Number (MPN) techniques. TBC and TCC were high and exceeded acceptable limits. Faecal coliforms, faecal Streptococciand Klebsiella species constituted 25% of the indicator organisms identified.The observed parameters indicated the Dam was contaminated with pathogenic bacteria. Variations in the weather conditions, animal and anthropogenic interferences were all directly or indirectly related to faecal contamination in the dam. Preventing indiscriminate faecal discharge close to the Dam and sufficient water treatment before consumption are of prime importance to public health as the dam was established for agricultural purposes. DOI: http://dx.doi.org/10.3126/ije.v3i2.10523 International Journal of the Environment Vol.3(2) 2014: 125-136